2018
DOI: 10.24105/apr.2018.5.19
|View full text |Cite
|
Sign up to set email alerts
|

The role of socioeconomic status and the development of congenital heart disease: A scoping review

Abstract: Introduction: Congenital heart disease (CHD) is the most common congenital anomaly affecting 1% of all live births of which the etiology remains unknown. The incidence is higher in developing countries likely related to low literacy, poverty and higher exposures to hazardous environmental nuisances. The role of socioeconomic status (SES) in CHD development has recently received attention. To gain the breadth of knowledge generated from existing publications, we undertook a scoping review of studies examining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Similarly, infants whose mothers lived in the neighbourhoods with the lowest percentage of people with a university or higher degree had a higher chance of CHD (adjusted OR: 1.34, 95% CI: 1.24-1.44) when compared to those living in the neighbourhoods with the highest percentage of people with a university of higher degree [14]. Studies from other countries showed similar results [22,23]. One recent study conducted in the United States found the incidence of CHD among infants to be higher in the most socially and economically disadvantaged neighbourhoods (quartile 4) compared to the least disadvantaged neighbourhoods (quartile 1) (adjusted OR 1.31, 95% CI: 1.21-1.41) [46].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Similarly, infants whose mothers lived in the neighbourhoods with the lowest percentage of people with a university or higher degree had a higher chance of CHD (adjusted OR: 1.34, 95% CI: 1.24-1.44) when compared to those living in the neighbourhoods with the highest percentage of people with a university of higher degree [14]. Studies from other countries showed similar results [22,23]. One recent study conducted in the United States found the incidence of CHD among infants to be higher in the most socially and economically disadvantaged neighbourhoods (quartile 4) compared to the least disadvantaged neighbourhoods (quartile 1) (adjusted OR 1.31, 95% CI: 1.21-1.41) [46].…”
Section: Discussionmentioning
confidence: 70%
“…A meta-analysis including data from 33 studies found that lower levels of maternal education and family income, and maternal exposure to certain occupations increased the risk of CHD by 11%, 5% and 51%, respectively [22]. However, the results were not consistent across all geographic areas and SES indicators [22,23]. The mechanism of this relationship remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, nonmedical health determinants have been shown to contribute to health and disease outcomes and lead to congenital anomalies [ 17 , 18 ]. Poverty, social exclusion, and unhealthy behaviors are associated with congenital anomalies such as congenital heart abnormalities, although in this regard, the results of research are different [ 10 ].…”
Section: Introductionmentioning
confidence: 99%